Comparison of Connective Tissue and Fascia in the Treatment of Maxillary Ridge Defects - Pazos Ruiz, Andreína; Pontificia Universidad Javeriana (Editorial Pontificia Universidad Javeriana, 2010)
Aim: Compare tissue grafting from autologous and allogenous sources for the treatment of Seibert Class I border defects. Methods: 18 surgical sites from 14 patients were selected and randomly assigned. 8 surgical sites received connective tissue grafts from autologous donor sites, and 9 surgical sites received allogenous muscular fascia grafts. 4 diagnostic casts were taken for comparative study (baseline, 1 month, 2nd month and 4th month postsurgical). In addition, 6 tissue punch biopsies were taken from the fascia group to determine presence of fascia tissue. Results: The control group showed an average tissue depth of 2.29 ± 0.55 mm and the experimental group showed 3.5 ± 0.85 mm, at baseline. Tissue gain for the fascia group was 71.2%, 46.52% y 28.5% for the 1st, 2nd and 4th months respectively, and the control group presented 56.53%, 38.31% y 38.1% respectively. There were not statistically significant differences between the two treatments (p>0,05). Histological analysis of the fascia group showed dense collagen tissue and host connective tissue at the 4th month. Fascia tissue grafts seemed to reabsorb faster than the connective tissue from the control group and the gain in tissue size at the 4th month was similar in both groups. The fascia tissue group, however, seemed to present less morbidity and was found in the histological samples at the 20 week postsurgical measurements. The connective tissue grafts were more stable in the treatment of Seibert I border defects. Conclusions: Human muscular fascia tissue could be an alternative treatment for the correction of Seibert class I border defects.